Assessment of eosinophils in gastrointestinal inflammatory disease of dogs. (7th October 2018) - Bastan, Idil; Rendahl, Aaron K.; Seelig, Davis; Day, Michael J.; Hall, Edward J.; Rao, Savita P.; Washabau, Robert J.; Sriramarao, P.
Abstract : Background: Accurate identification of eosinophils in the gastrointestinal (GI) tract of dogs with eosinophilic GI disease (EGID) by histological evaluation is challenging. The currently used hematoxylin and eosin (H&E) staining method detects intact eosinophils but does not detect degranulated eosinophils, thus potentially underrepresenting the number of infiltrating eosinophils. Objective: To develop a more sensitive method for identifying and quantifying both intact and degranulated eosinophils to diagnose EGID more accurately. Methods: Endoscopically obtained paraffin‐embedded intestinal biopsy specimens from dogs with GI signs were examined. The study groups were dogs with eosinophilic enteritis (EE), lymphoplasmacytic and mixed enteritis, and control dogs with GI signs but no histologic changes on tissue sections. Consecutive sections were immunolabeled with monoclonal antibodies (mAbs) against the eosinophil granule protein eosinophil peroxidase (Epx) and stained by H&E, respectively. The number of eosinophils was manually quantified and classified as intact or degranulated. Results: The number of intact eosinophils detected in Epx mAb‐labeled duodenal sections was significantly higher compared with that in H&E‐stained sections, with a similar relationship noted in the colon and stomach. The Epx mAb allowed the unique assessment of eosinophil degranulation. The number of intact and degranulated eosinophils was significantly higher in duodenal lamina propria of the EE and mixed group compared to the control group. Conclusion: Immunohistochemical detection of Epx provides a more precise method to detect GI tract eosinophils compared to H&E staining and could be used as an alternative and reliable diagnostic tool for assessment of biopsy tissues from dogs with EGID.